(untitled) (Bangladesh Agronomy Journal, 2018)
Soybean (Glycine max) seed loses its viability in the storage which causes shortage in supply of quality seed and consequently hinders the expansion of soybean cultivation in Bangladesh.Losses of seed viability of soybean (Glycine max) in traditional storage is very common in the tropical environment. An experiment was conducted at the Seed Laboratory, Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Jamalpur in 2011 and 2012 to find out the effect of seed moisture content and types of storage container on soybean seed germination and seedling vigour. In 2011, soybean seed having 94% initial germination was stored at 8, 10 and 12% moisture levels but in 2012 seeds having 96% initial germination was stored at 6, 8, 10 and 12% initial moisture levels in four different types of storage containers viz., polythene bag, plastic pot, tin can and glass jar. weredays after storage ().The experiment was arranged in a factorial completely randomized design with three replications. In 2011, high germination of soybean seed (77-85%) was retained at 200 DAS for those stored at 8% initial seed moisture content (SMC) in any of the containers. Germination index and seedling dry matter decreased with increased initial seed moisture content irrespective of storage containers used. Tin preserved higher seed moisture contents of 9.93, 11.71 and 14.15% for seed stored at 8%, 10% and 12% initial seed moisture content, respectively. In 2012, 80-94% seed germination was retained at 200 DAS for those stored at 6% initial SMC in any of the containers. The germination declined to a range between 75.0 and 91.3% within 200 DAS at 8% initial SMC while those stored at 12% SMC showed rapid germination loss and the value showed down to between 9.3 and 22.0%. Vigour index and seedling dry matter decreased with increased initial seed moisture content irrespective of storage containers used. Tin also Seeds stored in tin container showed the higher final seed moisture contents irrespective of initial seed moisture content. Bangladesh Agron. J. 2018, 21(1): 131-141